Foreword: A bright future for plaNext and the AESOP publishing platform - Giancarlo Cotella (PlaNext)
In early 2025, plaNext – Next Generation Planning achieved a significant milestone: its indexing in the Scopus database. This event marks a pivotal moment for the journal and for the broader publication strategy of the Association of European Schools of Planning (AESOP). It is a recognition of the collective efforts made by successive editorial boards, contributors, reviewers, and above all, by the young scholars who believed in a journal that could serve both as a platform for emerging voices and as a vehicle for innovation in planning scholarship. More than a celebratory note, this foreword seeks to situate plaNext within AESOP’s evolving ecosystem of publications and overall digital environment. It reflects on the journal’s distinctive role and achievements, connects it with the broader ambitions of AESOP’s scientific dissemination strategy, and explores how recent developments—including the launch of the AESOP Digital Archive—are contributing to a renewed and more integrated platform for publishing in planning.